Assessing the Impact of Ecofeminist Policy on Gender and Environmental Practices - Muhammad Asif; Yassine Chami; Mohamad Abou Adel; Mohammad Alhourani; Moustafa Abouelnour (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
Global environmental degradation and persistent gender inequality continue to challenge the achievement of sustainable development in Pakistan. Although Pakistan has ratified the Convention on the Elimination of All Forms of Discrimination Against Women and adopted the Sustainable Development Goals, the government still implements environmental and gender policies in a fragmented and sectoral manner. Policymakers continue to prioritize normative approaches that fail to address patriarchal domination, women’s marginalization, and environmental exploitation in an integrated framework. This study examines the urgency of strengthening ecofeminist policies within a sustainable socio ecological framework that promotes gender justice and environmental sustainability. The research applies a juridical normative method combined with a comparative policy approach through an examination of environmental governance practices in Pakistan and Sierra de Santa Rosa. The findings reveal that Pakistan has not established comprehensive policies capable of integrating gender equality with environmental governance. In contrast, Sierra de Santa Rosa implements a participatory and community-oriented model that enables women to contribute actively to environmental conservation, sustainable agriculture, and local economic development. This study concludes that Pakistan must strengthen gender responsive environmental governance by integrating institutions, encouraging community participation, increasing women’s involvement in decision making processes, and promoting cross sectoral collaboration to achieve long term socio ecological sustainability.